BS16. VNS in generalized epilepsy: An assessment on the efficacy. (May 2018) - Marti, Ana Suller; Parrent, Andrew; Mclachlan, Rick; Mirsattari, Seyed M.; Diosy, David C.; Steven, David; MacDougall, Keith W.; Burneo, Jorge G.
Abstract : Introduction: The VNS (Vagus Nerve Stimulation) is a type of neuromodulation therapy used in patients with focal epilepsy, usually reserved for those who are not candidates for resective surgery. The initial aprovation was for focal epilepsy. The range of seizure frequency reduction of 50% or more were 40% in the study of Panebianco et al. (2015) and 24.5–46.6% by Ben-Menachen et al. (2015). However, there is not clear evidence if it has the same effect in all types of epilepsy. Our aim is to assess how effective this treatment is in those with generalized tonic-clonic (GTC) seizures in the context of generalized epilepsy. Methods: We interrogated the database of the Epilepsy program at Western University and identified those patients with generalized epilepsy, who underwent VNS implantation, since this treatment became available in Canada, until March 2017. Results: 21 patients with the diagnosis of Generalized Epilepsy underwent VNS implantation in our center. In this group, the mean age of implantation was 27.3 years (range: 18–51 years), 12 patients (57%) were male. Mean follow up was 65.2 months (range: 7–192 months). The mean frequency of GTC seizures was 20.3 per month (0.5–120), and in patients with LGS of 51.5 per month (4–120). MRI was normal in 10, abnormal in 10 and 1 no information was available; in LGS cases: 3 generalized atrophy, 1 normal, 1 periventricular heterotpia, 1 porencephaly and atrophy several lobes in both hemispheres, microcephaly.5 patients had previous palliative surgery: 2 had partial callosotomy and 3 a complete one. Invasive recordings were performed in 3 patients, as there was a concern for possible focal epilepsy with raid spreading, but the results revealed generalized onset for their seizures. Other demographic and clinical characteristics are included in the table below. After the implantation, none of the patients was GTC seizure free. Seven (38.9%) had a more than 50% reduction in the frequency of GTC seizures. One patient developed an infection in the area that was implanted and required explantation. Ten (47.6%) developed cough, pain in the neck and/or hoarseness, but none required explantation. So far, 2 patients have required a change in battery, lasting an average of 114.5 months. Conclusion: VNS appears to be a therapy effective not only in focal epilepsy, but also in reducing the number of GTC seizures in those with generalized epilepsy. Also, VNS implantation has low risk of complication, without major side effects.